Echo or organic: framing the 2014 Sochi Games. Issue 6 (10th October 2016) - Frederick, Evan; Pegoraro, Ann; Burch, Lauren
Abstract : Purpose: The purpose of this paper is to perform a comparative analysis of how traditional media and social media framed the 2014 Sochi Winter Olympic Games. Design/methodology/approach: The researchers examined newspaper articles pertaining to the Sochi Olympics and Tweets containing #SochiProblems to determine if differences or overlap existed in terms of themes and frames. A thematic analysis was conducted with the qualitative software Leximancer. Findings: An analysis of 2, 856 newspaper articles and 497, 743 Tweets revealed three frames across the two media platforms including: the setting, the politics, and the games. There was both a divergence and convergence of content. While there was an echo chamber in terms of discussions regarding political controversies, organic content related to conditions and accommodations existed primarily on Twitter. Originality/value: This study sought to investigate whether organic content on Twitter could withstand the transference of sentiments that emerge in traditional media. This study adds to the current body of the literature by examining whether there is a convergence or divergence of content across media platforms pertaining to an international sporting event.